The Meaning of Happiness Among Single-Parent Family Students in Secondary School: A Phenomenological Study - Ahmad Fadil; Firyal Magi Ashil Jannah; Ina Kurniati (Journal of Psychology and Social Sciences, 2025)
Happiness is a fundamental goal for every individual, including students from single-parent families who face unique psychological and social challenges. However, previous research in Indonesia has predominantly focused on the negative impacts of non-intact family structures, with limited exploration of the subjective meaning of happiness among students from single-parent families. Addressing this gap, the present study explores the meaning of happiness among junior high school students raised in single-parent families in Indonesia through a qualitative phenomenological approach. Data were collected via semi-structured interviews with two purposively selected students from MTs Ma’arif Klaten. Thematic analysis identified that student happiness is shaped by both internal factors—such as coping strategies, personal resilience, and self-acceptance—and external factors, including emotional support from family (despite its non-intact structure), positive social relationships with peers and teachers, and a supportive school environment. These findings highlight that happiness for single-parent students is a dynamic process arising from the interplay between individual psychological resources and social support, rather than being determined solely by family intactness. The study recommends that schools, teachers, and counselors strengthen social support systems and develop inclusive, responsive psychosocial interventions to enhance the psychological well-being and optimal development of students from diverse family backgrounds.